The natural increase in the municipality of Kufra during the period (1995-2020), a study in population geography (Journal of Libya for geographical studies, 2023)
This study aimed to get to know the rate of natural increase in the municipality of al-kufra during the period from 1995 to 2020, and it knows if general trend of the rate of natural increase is going towards a decrease or an increase, Also, comparison between the rates in both Al-Jawf and Al-Hawari, and comparing with the rates in the State of Libya, to know if there are differences in rate, this in turn shows the effect of some local conditions in the rates. The results showed that the rate of natural increase in the municipality of Kufra is moving in a general downward trend. It is the same general trend of rates in the Al-Jouf area; this is the offsite of general trend of rate in the Hawari and Libya. Also, this study aimed to show effect of the natural increase in population growth.
Keywords: natural increase; al-kufra municipality; Al-Jawf; Al-Hawari; population geography; crude death rate; crude birth rate